UJI POTENSI EKSTRAK DAUN TANAMAN KETEPENG (Cassia alata L) DALAM MENGHAMBAT PERTUMBUHAN BAKTERI Ralstonia solanacearum dan Streptococcus sobrinus - Saat Egra; Mardiana Mardiana; Ana Kurnia; Kartina Kartina; Aditya Murtilaksono; Harlinda Kuspradini (Fakultas Kehutanan Universitas Mulawarman, 2019)
Ketepeng (Cassia alata L.) was a group of plants included in the Magnoliophyta division which can be found in tropical or subtropical areas. The purpose of this study was to determine the potential of Ketepeng leaves to inhibit the growth of R. solanacearum and S. sobrinus bacteria. The method used in this study is agar well diffusion with 3 replications. The sample used was Ketepeng leaf extract with several concentrations of 0.5%, 1%, 2%. Positive controls in this study were Chloramphenicol and negative control of 40% ethanol. The variables calculated are the calculation of water content, percentage of yield and percentage of area diameter barriers (DDH). In addition, the DDH results show the ethanol extract of Ketepeng leaves at concentrations of 0.5% and 1% not able to inhibit the growth of R. solanacearum, but at a concentration of 2% able to inhibit R.solanacearum with a diameter of 11,7 mm and the ethanol extract of Ketepeng leaves at concentrations was able to inhibit the growth of S. sobrinus bacteria with the highest diameter of 16 mm at a concentration of 2%.